Carbon nanotubes pickup by van der Waals force based on nanorobotics manipulation inside SEM - Yang, Zhan; Chen, Tao; Wang, Yaqiong; Sun, Lining; Fukuda, Toshio (Micro & Nano Letters, 2016)
A method of picking up carbon nanotubes (CNTs) from nanotube bulk by van der Waals force inside a scanning electron microscopy is presented. An atomic force microscope cantilever was employed as end effector of nanorobotics manipulators for CNT picking up. A manipulation strategy was established by analysing the van der Waals force of three different types of contacting models. Three groups of experiments were designed and carried out to investigate the effects of different factors. Factors including pickup angle, pickup contact area between the CNT and the cantilever and pickup speed of the end effector were discussed. The results shown that a pickup angle at 90.1° and a pickup speed lower than 10 nm/step with a pickup contact length more than 1.5 µm would increase the probability of picking up CNT successfully.